A cost optimised process mean set point for two sided specifications - Van Wijck, W.; Von Benecke, M. (SAIIE, 2012)
CITATION: Van Wijck, W. & Von Benecke, M. 1999. A cost optimised process mean set point for two sided specifications. South African Journal of Industrial Engineering, 10(1):87-98, doi:10.7166/10-1-375.